The Influence of Work Engagement and Perceived Organizational Support on Organizational Commitment - Rioe Chandra; Roswaty Roswaty; Shafiera Lazuarni (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine the effect of the variables of Work Involvement and Perceived Organizational Support on Employee Organizational Commitment at the Regional Financial and Asset Management Agency (BPKAD) of Banyuasin Regency, either partially or simultaneously. This study uses a quantitative approach by collecting data through survey methods. The data collection technique used in this study was a questionnaire. the existing population is employees of the Banyuasin Regency Regional Financial and Asset Management Agency (BPKAD), totaling 56 employees. This research uses saturation sampling technique. So that will be used as samples in this study are all of the population taken, namely all employees of the Regional Financial and Asset Management Agency (BPKAD) of Banyuasin Regency, totaling 56 people. Based on the results of data analysis, the results of this study indicate that there is an influence of the variables of Work Involvement and Perceived Organizational Support on Employee Organizational Commitment at the Banyuasin Regency Financial and Asset Management Agency (BPKAD) both partially and simultaneously. Based on the results of the calculation of the Coefficient of Determination, it can be concluded that there is 66.9% influence produced by the variables of Work Involvement and Perceived Organizational Support on Organisational Commitment